2016
DOI: 10.1051/matecconf/20179001014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat-treatment on the hardness and mechanical properties of Boron Alloyed Steel

Abstract: Abstract.In an automotive industry, hot stamped, die quenched structural components have been widely used to provide extra protection against crash intrusion. Boron alloyed steel exhibit limited ductility, but it also promotes improvement in impact performance. This study analyzed the effect of cooling rate on the hardness and energy absorption. Selfquenched specimens were heated to 850qC and cooled in air of room temperature, water at room temperature and cold water. Vickers hardness test and tensile test was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The hardness of material heated to a high degree and then cooled in oil was the same as that of unheated material, which was 139 HV. It can be shown from this experiment that heating mild steel to a high temperature and quickly cooling it with water increases its mechanical properties (hardness) by 24 It was reported by Khiyon and Salleh, [12] that the higher the cooling rate of the quenching, the smaller the size of the grain size. Hence, it will increase the hardness of the steel.…”
Section: Resultsmentioning
confidence: 63%
“…The hardness of material heated to a high degree and then cooled in oil was the same as that of unheated material, which was 139 HV. It can be shown from this experiment that heating mild steel to a high temperature and quickly cooling it with water increases its mechanical properties (hardness) by 24 It was reported by Khiyon and Salleh, [12] that the higher the cooling rate of the quenching, the smaller the size of the grain size. Hence, it will increase the hardness of the steel.…”
Section: Resultsmentioning
confidence: 63%
“…The fact can be explained by the most favourable conditions of a working environment attack on the T tube which multiply concentration is tens and hundreds of times higher than average corrosivity along walls. During operation, metal of well equipment tubes experiences cementite decay which keeps in step with the findings [11]- [15].…”
Section: Figure 6 Nature Of Microhardness Distribution Within the Cut...mentioning
confidence: 52%
“…Destructive capacity of a flow depends upon the content of reservoir water, the weighed mechanical impurities, and the flow velocity in a well. Analysis of mechanical impurities of oil wells have shown that the impurities mainly contain quartz sand (60-70%) characterized by the greatest hardness among the basic rocks of productive oil seams [9]. Hydrogen phase and significant amount of mechanical impurities with the prevailing sand fraction support the idea of the intensified corrosion processes [10].…”
Section: Introductionmentioning
confidence: 98%
“…It is known [8] that any thermal and hydraulic impact disturbs natural cementing connections in a reservoir; consequently, well products contain excessive amount of mechanical impurities which range in oil wells is 60-150 mg/l [9]. In such cases, GHMs cannot operate correctly within the sites.…”
Section: Introductionmentioning
confidence: 99%